2022
DOI: 10.3389/fpls.2022.870959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaCl2 Sprays in Different Fruit Development Stages on Grape Berry Cracking

Abstract: Grape cracking is a common phenomenon that can reach more than 50% in some varieties and can cause enormous economic losses. “Li Xiu” grapes in different developmental stages were treated with calcium chloride (5 g/L), and the cracking rate and related biochemical and genetic indices were measured in the fruit ripening stage. The results showed that calcium treatment during the flowering period could significantly reduce grape cracking. Based on the experimental results, there are several reasons as follows: f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Thus, ABA increases cellulase and polygalacturonase activity, playing a crucial role in berry abscission. However, preharvest treatments with CaCl2 on grapes significantly decreased ABA synthesis and reduced berry drop [9] and cracking [68]. In general, the major organic acids at harvest were tartaric (200-270 mg 100 mL -1 ) and malic in lower concentration (90-160 mg 100 mL -1 ) (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…Thus, ABA increases cellulase and polygalacturonase activity, playing a crucial role in berry abscission. However, preharvest treatments with CaCl2 on grapes significantly decreased ABA synthesis and reduced berry drop [9] and cracking [68]. In general, the major organic acids at harvest were tartaric (200-270 mg 100 mL -1 ) and malic in lower concentration (90-160 mg 100 mL -1 ) (Table 3).…”
Section: Resultsmentioning
confidence: 98%
“…In mandarin (Citrus reticulata Blanco) cv Nova, grown during dry hot summers in the Mediterranean basin, seasonal water deficit followed by heavy rain during the cell enlargement stage was also linked to fruit cracking (Almela and Agustı, 1990). development, and productivity (Seo et al, 2022).It has been reported that the mineral nutritional status of crop and, therefore, of fruits is closely related to fruit cracking (Shi et al, 2022). Among all the mineral elements necessary for the growth of orchards, calcium participates in numerous vital processes due to its role in the structural integrity and stability of the cell walls and middle lamella.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…The majority of studies addressing fruit cracking have focused on reducing fruit water potential and increasing fruit calcium content [ 21 ]. The objective of the calcium-based chemical applications is reduce water uptake through the fruit cuticle prior to rainfall [ 22 ]. Previous studies have demonstrated the efficacy of calcium applications in mitigating rain-induced cracking in sweet cherry [ 23 ] by strengthening cell walls [ 24 ].…”
Section: Introductionmentioning
confidence: 99%